EVALUASI PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KECAMATAN RUMBAI PESISIR - Arfan Dilando. D; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Evaluation of District Integrated Administration Service in Rumbai Pesisir Subdistrict undertaken to know the dynamics of the development of local government administration towards good governance, which concerns the needs and demands of society in public service. This is done to find out how far the success of PATEN in Rumbai Pesisir Subdistrict and what is the inhibiting factor in the implementation of PATEN in Rumbai Pesisir District. The research was conducted using qualitative method with descriptive research. This study uses the theory of service quality evaluation by Morgan and Morgtroyd in Warella, Y consisting of Realibility, Responsiveness, competence, acces, courtesy, communication, credibility, security, understanding the customer, appearance presentation. In this research, the techniques are observation, interview, and literature study by using descriptive analysis technique. The result of this research shows that PATEN evaluation in Rumbai Pesisir District can be said good. This is marked by friendly officers, simple and clear service procedures, timing of settlement in accordance with the standard of service, adequate facilities for the community, and cost in accordance with the information. In addition there are inhibiting factors that lack the delegation of authority of the Mayor To the head of sub-district, as well as improved hygiene and supporting equipment for the community and officers PATENT.Keywords: Evaluation, PATEN in Rumbai Pesisir